Histochemistry of the digestive gland of the pearl oyster Pinctada imbricata (Pterioida: Pteriidae) during the gametogenic cycle, Venezuela - Romero Fereira, Patricia (2016)
Histochemical techniques today allow you to select areas of tissue and generate reliable information on the distribution of energy reserves in bivalve molluscs during their life cycle. The main objective of this study was to describe and relate the gametogenic cycle with the availability of energy reserves and the environmental parameters. For this, we sampled and examined the gonads and digestive glands (DG) of 15 individuals collected monthly during April 2012 and February 2013. We processed and analyzed the samples by standard histological and histochemical light microscopy techniques. Our results showed that for the gametogenic cycle, the monthly proportion of mature organisms was higher for males, between August (40 %) and November (53 %), while the females tend to have a shorter synchronized cycle and release of gametes in September (67 %) and October (60 %). The intense spawning periods in both sexes was the same (October to January). Between the periods April-August 2012 and January-February 2013, we observed the highest values of IGl and glucide index (instead, a decrease was observed in September, reaching minimum values during the period October-December). Besides, the maximum values of IL, lipid index, were observed in April-2012 and February-2013, with an intermediate value in August-2013. The results indicated that the reserves of the GD have a pattern of mobilization inversely related to the proliferation of gametes in both sexes; this was directly linked to the availability of nutrients such as chlorophyll a and the organic seston.